Pengaruh Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian (Studi Kasus pada Usaha Dagang Keripik Buah “Mekar Sari” di Desa Tlogo III, Kecamatan Kanigoro, Kabupaten Blitar) - Riska Nindia Sari; Wulan Destari Natalia (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2021)
Trading business is able to win the competition if it can have products according to customer wants and needs and can convey the advantages of its products to consumers. There are several aspects that can influence consumer decision making to buy products, including quality products and company promotion activities. This exploration was directed at the "Mekar Sari" Fruit Chips Trading Business in Dd. Tlogo III, Kec. Kanigoro, Kab. Blitar. This examination means to decide the impact of item quality and promotion on purchasing decisions. The methodology utilized is a quantitative research method using a questionnaire. The population used is the consumer in Mekar Sari Fruit Chips Trading Business. Meanwhile, to analyze the data used the validity test using the product moment, and Croncbach's Alpha as a reliability test. To test the prerequisite analysis used normality testing and heteroscedasticity test. Then in testing the hypothesis the T partial test is used. The consequences of this examination were gotten dependent on the calculation of the T test with the coefficient of sig. From product quality to purchasing decisions, it produces a value of 0.000 <0.05, which means that the increasing quality of the product causes an increase in purchasing decisions. And the sig. promotion of purchasing decisions produces a number of 0.003 <0.05, which implies that the better the promotion, the better the purchasing decision.